O desenvolvimento do conceito de pensamento computacional na educação matemática segundo contribuições da teoria histórico-cultural - Navarro, Eloisa Rosotti (2021)
The objective of this research was to develop, from conceptual nexuses and assumptions of Cultural-Historical Theory, the theoretical concept of computational thinking for its development in Mathematics Education. The research is characterized as qualitative. The logical-historical movement of the term “computational thinking” was analyzed through a State of Knowledge type of study, in the period from 2009 to 2019, with data from research (theses and dissertations), scientific articles, the Base Nacional Comum Curricular (BNCC), and the Curriculum of the State of São Paulo, called Currículo Paulista. Thus, the following leading question was established: What are the possible conceptual nexuses that contribute to the development of computational thinking in the context of Mathematics Education? The results point out that there are studies that use the term and diverge in relation to the definition of computational thinking and its characteristics. In addition, the analysis of the aforementioned documents allowed, under the aegis of Cultural-Historical Theory, to determine three conceptual nexuses of computational thinking, which can be configured in the context of Mathematics Education and, consequently, in school Mathematics, which are: problem solving; algebraic thinking, and algorithmic thinking. These conceptual nexuses are, essentially, in constant movement, as they are dialectical, historical, logical, and cultural. Based on them, the concept of computational thinking was developed in Mathematics Education, which considers the essentiality of developing computational thinking as a potential means of expanding the skills of problem-solving, of interpreting reality, and of expanding the ways of action of students in their sociocultural context, either in a plugged (ICTs) or unplugged manner. In this sense, the definition of the concept aims not only to think about “what it is” (external nexuses), but “how we can use it in everyday school life” and “how it can be developed to interpret and solve problems in reality” (internal nexuses). The logical-historical movement of computational thinking corroborates the development of this type of thinking, in its connection with the act of appropriation and use by students.